Valuation of Forest Crops-the Concept of Price Increase - Mishra, P. (Indian Forester, 1977)
Forest Officers are quite often called Upon to work out the compensation, which has to be charged from the party is whose favour the forest land is released. The application of Foustmann’s Formula for determining the espectation value of immature crops has been discussed. The author has pointed out that it would not be correct to accept the present value of the mature crops and thinning products while applying this formula. The price increase during the period when the crop will mature for felling has to be ascertained from the past market trends and the values of final crop and the intermediate yields worked out at the computed rates.